Determination of total contents of transition metals in selected granular black teas marketed in Poland - Sekuła, Anna; Brodowska, Katarzyna; Więdłocha, Marzenna (Biotechnology and Food Science, 2014)
The total contents of metals in three granulated black tea samples marketed in Poland were determined. Four elements consisting transition metals (Ni, Cu, Zn and Fe) were analyzed using flame atomic absorption spectrophotometry (FAAS). All examined tea brands contain considerable contents of the studied transition metals. Among the tested transition metals Fe (242-589 mg kg-1) was the most abundant one in the granular black tea imported from India. The highest value of Fe was analyzed in the cheapest tea, the smallest in the most expensive. The other metals are less abundant than Fe, their values varied from 8.50-8.90 for Ni, 7.80-10.4 for Cu and 8.13-12.6 for Zn mg kg-1. The accuracy of the proposed method was assessed by determining the recovery of metals from analyzed tea samples using the standard addition method. Recovery assays of nickel, copper, zinc and iron were demonstrated satisfactory, mean recoveries 99.29, 100.31, 99.94 and 99.79 %, respectively.